2015
DOI: 10.1021/acs.iecr.5b02195
|View full text |Cite
|
Sign up to set email alerts
|

Biobased Heat-Triggered Shape-Memory Polymers Based on Polylactide/Epoxidized Natural Rubber Blend System Fabricated via Peroxide-Induced Dynamic Vulcanization: Co-continuous Phase Structure, Shape Memory Behavior, and Interfacial Compatibilization

Abstract: A biobased heat-triggered shape memory polymer (HSMP) consisting of polylactide (PLA) and epoxidized natural rubber (ENR) was fabricated by peroxide-induced dynamic vulcanization. The crosslinked ENR phase exhibits a continuous net-like structure embedded in the PLA phase, which is different from conventional plastic/rubber system having typically "sea-island" morphology in which vulcanized rubber particles dispersed in plastic matrix. In-situ interfacial compatibilization was confirmed by FTIR analysis. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 45 publications
1
54
0
Order By: Relevance
“…Considering the fact that blends of TPU and ABS are immiscible, introduction of ABS‐g‐MAH as a compatibilizer can seriously affect shape memory behavior of the blends. Presence of ABS‐g‐MAH improves interfacial adhesion between TPU and ABS evidently, which affects stress‐transferring throughout the shape recovery .…”
Section: Resultsmentioning
confidence: 99%
“…Considering the fact that blends of TPU and ABS are immiscible, introduction of ABS‐g‐MAH as a compatibilizer can seriously affect shape memory behavior of the blends. Presence of ABS‐g‐MAH improves interfacial adhesion between TPU and ABS evidently, which affects stress‐transferring throughout the shape recovery .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a novel morphology structure in dynamically vulcanized TPVs was reported by Chen et al They found that the cross‐linked rubber phase exhibited a continuous net‐like structure in dynamically vulcanized PLA/NR and PLA/ENR systems . A cocontinuous structure was formed, which was beneficial to obtain outstanding shape memory effect …”
Section: Introductionmentioning
confidence: 96%
“…6,7 The effective way to prepare TPVs is through dynamical vulcanization, [8][9][10] which is the process of cross-linking an elastomer during its melt mixing with a molten plastic under dynamic condition. 11,12 A significant number of TPVs are produced through this method, such as polylactide (PLA)/natural rubber (NR), 13,14 PLA/epoxidized natural rubber (ENR), [15][16][17] PLA/nitrile butadiene rubber (NBR), 18 poly(vinylidene fluoride) (PVDF)/acrylic rubber (ACM), 19 ethylene-propylene-diene monomer (EPDM)/polypropylene (PP), [20][21][22][23] PVDF/ENR, 24 polyamide 12 (PA12)/hydrogenated acrylonitrile butadiene rubber (HNBR), 25 and ethylene octene copolymer (EOC)/poly dimethyl siloxane (PDMS) rubber. 26 The properties of TPVs strongly depended on the final morphology, which were affected by many factors, such as the cross-linking degree of the rubber phase, composition, viscosity and elasticity of individual components, preparation method, and processing condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SMPs gain a rising attentions from both scientific and technological fields with the requirements for more diverse and intelligent demands. Stimuli manner evolved from the direct heating to remote heating like light, magnetism, and electricity, from thermal manner to athermal manners, physical manner, and chemical manner and so on, dramatically promoting the applications of SMPs. However, the traditional thermal products can memorize just two shapes, namely, dual‐SMPs (DSMPs) and the programmed shape varies only in one‐way model from "B → A", neither more temporary shapes nor the two‐way model "A ↔ B" upon cyclic stimulus are expected for traditional DSMPs.…”
Section: Introductionmentioning
confidence: 99%